2016
DOI: 10.1002/cite.201500128
|View full text |Cite
|
Sign up to set email alerts
|

Produktion und Charakterisierung von mikrostrukturierten Calcitpartikeln aus der Kalkalge Emiliania huxleyi

Abstract: Biogene Calcitpartikeln (Coccolithen) aus Mikroalgen verfügen über hochkomplexe, dreidimensionale Strukturen, die so bei technischen Partikeln noch nicht bekannt sind. Es ist daher lohnenswert, Coccolithen in Bezug auf eine potenzielle industrielle Anwendung zu untersuchen. Diese Arbeit stellt einen effizienten phototrophen Bioprozess zur Gewinnung von Coccolithen vor und gibt einen Einblick in das Anwendungspotenzial dieser außergewöhnlichen Partikeln.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 94 publications
(124 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, it has been reported that coccoliths from cultivation are often malformed or partially destroyed, which may be caused by turbulence or potential toxic influence of the cultivation vessel . However, just recently the development of a functioning process, which delivers more than 5 g/L of coccoliths, was finally achieved . Although adequate quantity is the first requirement to perform material‐intensive measurements, more prerequisites have to be fulfilled in advance.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that coccoliths from cultivation are often malformed or partially destroyed, which may be caused by turbulence or potential toxic influence of the cultivation vessel . However, just recently the development of a functioning process, which delivers more than 5 g/L of coccoliths, was finally achieved . Although adequate quantity is the first requirement to perform material‐intensive measurements, more prerequisites have to be fulfilled in advance.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, microalgal responses to macronutrient starvation have often been investigated regarding the ecophysiology of these microbes. However, stagnating growth due to nutrient starvation does not necessarily shut down calcification and thus often leads to a relative overproduction of coccoliths (Paasche 1998;Dyhrman et al 2006), which is an interesting fact to biotechnologists that aim to exploit this biological function (Hariskos et al 2016).…”
mentioning
confidence: 99%